HUBUNGAN ASUPAN ZAT BESI DAN VITAMIN C, FREKUENSI KONSUMSI MINUMAN BERISIKO, DAN PERILAKU DIET DENGAN ANEMIA DEFISIENSI BESI REMAJA PUTRI SMAN 6 DEPOK - Aulia Dewi Fitripancari (2023)
Anemia is a condition where the hemoglobin level is lower than normal. In Indonesia, anemia is a nutritional disorder that is often found in schools. Purpose: To determine the relationship between intake of iron, vitamin C, frequency of consumption of risky drinks, and dietary behavior with the incidence of iron deficiency anemia in female adolescents at SMAN 6 Depok. Methods: Quantitative study using a cross-sectional research design. The sample used was 123 young female respondents aged 16-18 years using stratified random sampling. Data regarding patterns of consumption of iron and vitamin C and frequency of consumption of risky drinks were obtained through interviews using the SQ-FFQ and FFQ sheets. Dietary behavior data of female students were obtained from filling out questionnaires and Hb levels were obtained by taking data directly by nursing undergraduate students. Results: The results of univariate analysis showed that the incidence of anemia at SMAN 6 Depok was 13%. The results of bivariate analysis using the chi-square test showed a relationship between iron consumption pattern (p=0.016), vitamin C consumption pattern (p=0.0245), and dietary behavior (p=0.024) and there was no relationship between tea consumption frequency (p= 1,000), frequency of coffee consumption (p=1,000) with the incidence of iron deficiency anemia in female adolescents at SMAN 6 Depok. Conclusions: Adolescent girls need to increase awareness of the incidence of anemia and improve prevention behavior by paying attention to intake of iron and vitamin C, limiting consumption of tea and coffee as Fe inhibitors, and adopting healthy dietary behaviors.